2020
DOI: 10.3389/fnagi.2020.571437
|View full text |Cite
|
Sign up to set email alerts
|

Differential Circulating Levels of Naturally Occurring Antibody to α-Synuclein in Parkinson’s Disease Dementia, Alzheimer’s Disease, and Vascular Dementia

Abstract: Background: Aggregation of alpha-synuclein (α-Syn) is considered to be a significant pathological hallmark and a driving force of Parkinson's disease (PD). PD dementia (PDD) occurs in a substantial number of PD patients. Naturally occurring antibody against α-Syn (NAb-α-Syn) exists ubiquitously in human blood and is reported to be altered in PD. However, it is not clear yet whether PDD had similar changes of circulating NAb-α-Syn. Methods: In this study, we recruited 61 PDD patients, 52 patients with Alzheimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Two studies showed similar serum/plasma aSyn levels in patients with DLB and controls [ 60 , 61 ], while another three showed increased [ 53 , 69 , 70 , 71 ] and decreased [ 70 ] aSyn in DLB patients. Concerning patients with PDD, three studies have shown increased serum/plasma aSyn [ 53 , 57 , 69 ], one study showed decreased aSyn [ 72 ], and another showed a lack of differences when compared with healthy controls [ 24 ]. Kronimus et al [ 73 ] described lower serum aSyn levels in patients with PDD compared with non-demented PD patients.…”
Section: Studies Addressing Serum/plasma Asyn Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies showed similar serum/plasma aSyn levels in patients with DLB and controls [ 60 , 61 ], while another three showed increased [ 53 , 69 , 70 , 71 ] and decreased [ 70 ] aSyn in DLB patients. Concerning patients with PDD, three studies have shown increased serum/plasma aSyn [ 53 , 57 , 69 ], one study showed decreased aSyn [ 72 ], and another showed a lack of differences when compared with healthy controls [ 24 ]. Kronimus et al [ 73 ] described lower serum aSyn levels in patients with PDD compared with non-demented PD patients.…”
Section: Studies Addressing Serum/plasma Asyn Levelsmentioning
confidence: 99%
“…Several studies have shown similar serum aSyn levels [ 11 , 62 , 70 ] or antibodies against aSyn levels [ 20 , 69 , 72 ] in patients with Alzheimer’s disease (AD) [ 11 , 20 , 62 , 69 , 70 , 72 ] and similar serum aSyn antibodies levels in patients with vascular dementia [ 69 , 72 ] than those of healthy controls. In contrast, other studies described increased plasma aSyn levels in patients with AD compared with healthy controls [ 57 , 76 ], and another two studies showed increased autoantibodies against aSyn in AD patients [ 36 , 71 ], although fewer than those found in PD patients [ 71 ].…”
Section: Studies Addressing Serum/plasma Asyn Levelsmentioning
confidence: 99%